The global constitutionalization of human rights: Overcoming contemporary injustices or juridifying old asymmetries?. (March 2016) - Leite Gonçalves, Guilherme; Costa, Sérgio
Recent decades are marked by an impressive expansion of actors and legal structures intended to globally extend a certain 'Western' catalog of human rights. Recently, too, legal scholars have developed concepts to justify normatively the expansion of human rights (e.g. Habermas, Walker, Koskenniemi). This article reviews recent legal literature on global constitutionalization of human rights to reveal its blind spots, at two levels: i) the reaffirmation of European precedency for establishing the sources of human rights and ii) a lack of sociological tools for describing interpenetrations between law, power and social inequalities. In order to empirically illustrate these objections, the article analyses the recent global expansion of human rights of minorities, using two examples: cases treated by the Inter-American Court of Human Rights and the Brazilian legalization of ancestral territories of afro-descendants. Finally, the article argues for a decentered perspective that (at the local level) connects human rights with concrete claims for justice.